2013
DOI: 10.1007/s13277-012-0638-2
|View full text |Cite
|
Sign up to set email alerts
|

High intratumoral expression of fibroblast activation protein (FAP) in colon cancer is associated with poorer patient prognosis

Abstract: -An active stroma is important for cancer cell invasion and metastasis. We investigated the expression of fibroblast activation protein (FAP) in relation to patient prognosis in colorectal cancer. Colorectal cancer specimens from 449 patients were immunohistochemically stained with a FAP antibody and evaluated in the tumor center and tumor front using a semiquantitative four-level scale. FAP was expressed by fibroblasts in 85–90 % of the tumors examined. High versus no/low expression in the tumor center was as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
106
3
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(125 citation statements)
references
References 27 publications
8
106
3
8
Order By: Relevance
“…Furthermore, this process degrades local extracellular matrix components that are required for cell migration and matrix invasion during tumor invasion, angiogenesis and metastasis (21). Previous studies have revealed that seprase overexpression was evident in stromal fibroblasts and tumor cells in invasive breast, gastric, colonic and cervical carcinomas; however, it was absent or undetectable in all normal tissue cells, with the exception of cells involved in the early stages of wound healing (22)(23)(24)(25). In addition, an in vivo study using a mouse model of human breast cancer, demonstrated that seprase increased microvessel density and promoted rapid tumor growth (26).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this process degrades local extracellular matrix components that are required for cell migration and matrix invasion during tumor invasion, angiogenesis and metastasis (21). Previous studies have revealed that seprase overexpression was evident in stromal fibroblasts and tumor cells in invasive breast, gastric, colonic and cervical carcinomas; however, it was absent or undetectable in all normal tissue cells, with the exception of cells involved in the early stages of wound healing (22)(23)(24)(25). In addition, an in vivo study using a mouse model of human breast cancer, demonstrated that seprase increased microvessel density and promoted rapid tumor growth (26).…”
Section: Discussionmentioning
confidence: 99%
“…Prominent presence of CAF FAP in the stroma of solid tumors is correlated to a poor prognosis in colon carcinoma and pancreatic adenocarcinoma [26,27] …”
Section: Fibroblast Activation Protein αmentioning
confidence: 99%
“…Specifically, seprase is up-regulated in infiltrating ductal carcinomas of the breast and in resulting tumor metastases (19) as well as in peritoneal metastases in ovarian cancer (16,20). Increased seprase expression has also been associated with a more aggressive disease state in colon cancer (21,22), in osteosarcoma (23), and with lymph node metastases in human colorectal (14), pancreatic (24), and gastric cancers (25).…”
mentioning
confidence: 99%